Proteção às crianças e aos adolescentes em processo de escolarização à luz dos direitos humanos: o serviço de convivência e fortalecimento de vínculos - Lopes, Maria do Socorro Estrela (2014)
This work had the analysis of social protection measures as its object, in their relation with the process of schooling of children and adolescents and its main goal was to analyze the effects of the service of companionship and strengthening of bonds, in the schooling of children and adolescents in the rural community of Odilândia, in SantaRita/PB. Using the principles and theoretical reference of the Human Rights as a reference, the study sought to identify the students‟ school development after the implantation of the SCFV, aiming to measure its possible contributions and to guarantee students‟ insertion, reinsertion and permanence at school. In total, 12 people participated in this research, 6 adolescents and 6 educators. The instrument used was the semi-structured interview and with it, it was possible to obtain information about these people‟s everyday life with the programs PETI and “Projovem Adolescente”. Besides the interviews, the study also used institutional documents such as reports and planning regarding the SCFV (data obtained from the Brazilian System of Protection and Income Transference Programs), the school (students‟ frequency, students who pass, fail and evade) and the IDEB (result s of the evaluation of “Provinha Brasil”, done by second-grade students and “Prova Brasil”, for fifth to ninth-grade students at Arnaldo Bonifácio School). The research had a qualitative character and used as its theoretical-methodological reference the critical thinking and the presuppositions of the human rights such as: democracy, plain citizenship, right to human and intellectual development and to social policies. In order to do so, the following analysis indicators were adopted: insertion, permanence and frequency at school and at SCFV; the intersections between these policies; students‟ level of learning, number of students who pass and fail; and the separation from SCFV and returning to work. The information regarding the interviews, as well as all of the documents were systematized and analyzed using the technique of content analysis proposed by Bardin (1977). Lastly, concerning the difficulties observed at the school, it was evident that the combination of governmental measures and strategies, such as the Income Transference Programs (PETI and PBF) and “Projovem Adolescente” (currently SCFV) didn‟t result in the assessment of the problems related to children‟s and adolescents‟ schooling, presenting a disconnection and disarticulation with the reality of the rural community in the activities performed, depriving preventing and anticipatory actions from their character and not guaranteeing their definitive separation from work.